Recoleccion de germoplasma de Phaseolus en Bolivia, Abril 23 - Mayo 14, 1988 - Debouck, Daniel G. (International Center for Tropical Agriculture, 1988)
Eighty-nine samples of Phaseolus germplasm were collected during a three-week exploration in the eastern slopes of the Bolivian Andes. Of particular interest are: 12 samples of lima bean, 4 samples of wild P. vulgaris and 64 samples of common bean landraces. Some problems related to the origin of the cultigens, to the formation of three classes of landraces in common bean, are discussed, as well as the mechanisms by which their diversity is produced. (AS)